2015
DOI: 10.2135/cropsci2014.08.0544
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Seed Phytic Acid Concentration and Iron Bioavailability in a Pea Recombinant Inbred Line Population

Abstract: Phytate, the storage form of P in seeds, is not well digested by monogastrics, thereby contributing to micronutrient deficiency, decreased feed efficiency, and environmental pollution. This research was aimed at developing a single nucleotide polymorphism (SNP) based genetic linkage map and mapping genomic regions associated with phytic acid‐phosphorus (PA‐P) concentration using a recombinant inbred line (RIL) population (PR‐15) derived from a cross between a low phytate (low phytic acid [lpa]) mutant pea (Pis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Ma et al [ 36 ] reported that the QTL with highest explanation of phenotypic variance for seed zinc concentration in a mapping population derived from Aragorn x Kiflica tested in two different locations was also located on LG3. Shunmugam et al [ 50 ] also reported a major QTL for seed phytate concentration in pea on LG5, and this QTL was confirmed here using an expanded set of markers.…”
Section: Discussionsupporting
confidence: 83%
“…Ma et al [ 36 ] reported that the QTL with highest explanation of phenotypic variance for seed zinc concentration in a mapping population derived from Aragorn x Kiflica tested in two different locations was also located on LG3. Shunmugam et al [ 50 ] also reported a major QTL for seed phytate concentration in pea on LG5, and this QTL was confirmed here using an expanded set of markers.…”
Section: Discussionsupporting
confidence: 83%
“…Tremendous efforts have been made to delve deeper into the complex genetic architecture of this trait in several crop species, including cereals and legumes 2 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 . Among legumes with much emphasis on common bean, attempts have been made to decipher the underlying genetic factors regulating Fe and Zn concentrations in seeds of Medicago , lentil, field pea and chickpea 8 9 13 14 20 21 22 23 24 .…”
mentioning
confidence: 99%
“…The concentration of phytate P was reduced by ∼60% in 1‐2347‐144 and 1‐150‐81 compared with CDC Bronco. Along with low phytate acid P (PA‐P) concentration, there was a commensurate increase in inorganic P (P i ) (Shunmugam et al, 2015) The two low‐phytate lines, 1‐2347‐144 and 1‐150‐81, produced grain yield 92 and 86% of CDC Bronco, respectively (Delgerjav, 2012). From a nutritional standpoint, FeBIO was up to 1.9 times higher in the two low‐phytate lines than CDC Bronco (Liu et al, 2014).…”
mentioning
confidence: 99%